A K+-sensitive AND-gate dual-mode probe for simultaneous tumor imaging and malignancy identification. Issue 7 (28th April 2022) - Wang, Qiyue; Li, Fangyuan; Liang, Zeyu; Liao, Hongwei; Zhang, Bo; Lin, Peihua; Liu, Xun; Hu, Shen; Lee, Jiyoung; Ling, Daishun
Abstract: Although molecular imaging probes have the potential to non-invasively diagnose a tumor, imaging probes that can detect a tumor and simultaneously identify tumor malignancy remain elusive. Here, we demonstrate a potassium ion (K + ) sensitive dual-mode nanoprobe (KDMN) for non-invasive tumor imaging and malignancy identification, which operates via a cascaded 'AND' logic gate controlled by inputs of magnetic resonance imaging (MRI) and fluorescence imaging (FI) signals. We encapsulate commercial K + indicators into the hollow cavities of magnetic mesoporous silica nanoparticles, which are subsequently coated with a K + -selective membrane that exclusively permits the passage of K + while excluding other cations. The KDMN can readily accumulate in tumors and enhance the MRI contrast after systemic administration. Spatial information of the tumor lesion is thus accessible via MRI and forms the first layer of the 'AND' gate. Meanwhile, the KDMN selectively captures K + and prevents interference from other cations, triggering a K + -activated FI signal as the second layer of the 'AND' gate in the case of a malignant tumor with a high extracellular K + level. This dual-mode imaging approach effectively eliminates false positive or negative diagnostic results and allows for non-invasive imaging of tumor malignancy with high sensitivity and accuracy. Abstract : A potassium ion (K + ) sensitive dual-mode nanoprobe with superior magnetic resonance contrast effect and K + -specific fluorescence imaging performance is developed for non-invasive tumor imaging and malignancy identification.